Preventing history: a lexicographical learning-curve - Greenberg, D (2010)
Jowitt's Dictionary of English Law was about to become history, being allowed to slip slowly but surely into obsolescence after a lapse of more than 30 years between editions. An unlikely combination of impulses from its former publisher and a legal book-sellers gave it a final chance of revival, and a decision was taken to make one attempt to reverse the terminal decline. An editorial team was assembled, for membership of which the only lexicographical qualification was enthusiasm. In the course of the 3-year project we all learned a great deal about how not to write dictionaries. This short paper will offer some thoughts from a novice on how to grapple, at speed and against a host of commercial and professional pressures, with fundamental issues that will be familiar to experienced lexicographers. How do you brind yourself to throw out historical material that once gone will be found nowhere else? If you keep it, how do you prevent it from swamping the work of jeopardising the reputation of the dictionary? How do you draw the line between a good dictionary and a bad encyclopaedia? Is the inclusion of examples a counsel of perfection or an admission of failure to define clearly? How far is it worth striving for consistency, when the authority of the work depends on using a wide range of experts with necessarily individual styles and approaches? How far should one consolidate historical doubt, or strip out old entries simply because they are no longer verifiable (and perhaps never were)? How do you reflect the fact that the inclusion of new substantive fields changes the class of reader and, therefore, the kind of product they are expecting and need? And, finally, what is a dictionary anyway?